Toxic hepatitis caused by the excretions of the Phyllomedusa bicolor frog – a case report - Joanna, Pogorzelska; Łapiński, Tadeusz W. (Clinical and Experimental Hepatology, 2017)
The Kambô ritual consists of various types of skin scarification and subsequent application of Phyllomedusa bicolor secretion to the fresh wounds. In Europe, the ritual of Kambô is becoming more popular, but its use can lead to serious multiple organ damage, sometimes life-threatening. Our manuscript shows a patient with toxic liver damage probably associated with the Kambô ritual.